2018
DOI: 10.1002/jcb.26501
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypoxic preconditioning prevents palmitic acid‐induced cardiomyocyte apoptosis via switching metabolic GLUT4‐glucose pathway back to CD36‐fatty acid dependent

Abstract: Metabolic syndrome is a risk factor for the development of cardiovascular diseases. Myocardial cell damage leads to an imbalance of energy metabolism, and many studies have indicated that short-term hypoxia during myocardial cell injury has a protective effect. In our previous animal studies, we found that short-term hypoxia in the heart has a protective effect, but long-term hypoxia increases myocardial cell injury. Palmitic acid (PA)-treated H9c2 cardiomyoblasts and neonatal rat ventricle cardiomyocytes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Hypertension is a global multiple disease, the prevalence of the elderly is increasing year by year, and hypertrophy of the cardiac muscle caused by constant stress overload is a bad outcome of it. Hypertension can cause changes in myocardial energy metabolism, and these changes rapidly reduce the oxidation rate of fatty acids and its enzymatic expression and activity [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is a global multiple disease, the prevalence of the elderly is increasing year by year, and hypertrophy of the cardiac muscle caused by constant stress overload is a bad outcome of it. Hypertension can cause changes in myocardial energy metabolism, and these changes rapidly reduce the oxidation rate of fatty acids and its enzymatic expression and activity [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study demonstrated that LNMICC accelerated metastasis by reprogramming fatty acid metabolism in cervical cancer [22]. CD36 is a receptor for lipids and fatty acids and plays an important role in metabolic syndrome and related cardiac activities, which involved in lipid metabolism, long-chain fatty acid adsorption, apoptotic residue clearance, and macrophage phagocytosis [2325]. Studies have found that CD36-regulated fatty acid metabolism is closely related to tumorigenesis and development [26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids not only cause fat accumulation and inammatory reaction in liver cells in vitro but also induce insulin resistance 33 and impair glucose transport and glucose metabolism. 34 In our present research, we discussed that intracellular glycogen synthesis was increased by Nifu in HepG2 cells aer PA treatment. In addition, PA treatment was found to result in a signicant increase in the protein and mRNA expression of PEPCK and G6Pase, which are key gluconeogenesis enzymes.…”
Section: Discussionmentioning
confidence: 67%